Dysregulation of RasGRP1 in rheumatoid arthritis and modulation of RasGRP3 as a biomarker of TNFα inhibitors - Golinski, Marie-Laure (Arthritis Res Ther, 2015)
BACKGROUND: B and T cells play a key role in rheumatoid arthritis (RA) pathophysiology. RasGRP1 and RasGRP3 are involved in T and B cell receptors signaling, and belong to gene combination able to predict infliximab responsiveness, leading to the question of RasGRP1 and RasGRP3 involvement in RA. METHODS: RasGRP1 and RasGRP3 expression levels were measured by qRT-PCR and/or western-blot in peripheral blood mononuclear cells (PBMCs), in T and B cells from untreated RA patients and in RA patients treated by TNFα inhibitors. T and B cells from healthy controls (HC) were cultured with TNFα, and TNFα receptors neutralizing antibodies to highlight the TNFα effects on RasGRP1 and RasGRP3 pathways. MAPK pathways and apoptosis were respectively analyzed using the Proteome Profiler arrays and flow cytometry. RESULTS: In PBMCs from RA patients, gene expression levels of RasGRP1 were invariant while RasGRP3 was downregulated under TNFα inhibitors and upregulated under TNFα. In T cells from RA patients, RasGRP1 was decreased and its gene expression level was correlated with disease activity. In T cells from HC, TNFα stimulation increased RasGRP1 gene expression level while it reduced RasGRP1 protein expression level. Bryostatin-1 experiments have confirmed that the TNFα effect observed on T cells proliferation was due to the decrease of RasGRP1 expression. Besides, RasGRP3 expression level increased in PBMCs from RA patients under TNFα and in B cells from HC leading us to conclude that RasGRP3 in B cells was modulated by TNFα. CONCLUSION: This study demonstrates RasGRP1 dysregulation in RA patients while RasGRP3 is characterized as a biomarker linked to TNFα inhibitors. After binding to TNFR1, TNFα reduced RasGRP1 protein expression resulting in inhibition of T cell activation. TRIAL REGISTRATION: Clinicaltrials.gov NCT00234234, registered 04 November 2008; NCT00767325, registered 05 October 2005. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-015-0894-9) contains supplementary material, which is available to authorized users.